Konstruksi Politik Identitas Dalam Kampanye Politik Melalui Media Sosial Ganjar Pranowo dan Mahfud MD Menjelang Pemilihan Presiden Tahun 2024 - Azzura, Davena Rasyafa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this research is to see the construction of identity politics in the political campaign of Ganjar Pranowo and Mahfud MD ahead of the 2024 Presidential Election through social media. By using the theory of Primordialism, Constructivism, and Instrumentalism from Pierre Van Den Bergh. This research analyzes how political identity is built and used to attract mass support. Campaigns through social media such as TikTok, Instagram, and Youtube show direct interaction with the public, which allows the formation of identity politics based on religion, ethnicity, and political vision and mission. The results show that social media is an effective campaign tool in building identity politics and bringing candidates closer to voters.